A model for the automatic mapping of tasks to processors in heterogeneous multi-cluster architectures - De Giusti, Laura Cristina (2007)
This paper discusses automatic mapping methods for concurrent tasks to processors applying graph analysis for the relation among tasks, in which processing and communicating times are incorporated. Starting by an analysis in which processors are homogeneous and data transmission times do not depend on the processors that are communicating (a typical case in homogeneous clusters), we progress to extend the model to heterogeneous processors having the possibility of different communication levels, applicable to a multicluster. Some results obtained with the model and future work lines are presented, particularly, the possibility of obtaining the required optimal number of processors, keeping a constant efficiency level.